A sturm separation theorem for a linear 2n th order self-adjoint differential equation. (1995) - Fulton, Charles T.; Wu, Limin; Pruess, Steven
Abstract : For the 2 n th order equation, ( − 1 ) n v ( 2 n ) + q v = 0, with q continuous, we obtain a Sturm Separation theorem, involving n + 1 solutions of the equation, which is somewhat analogous to the classical result that the zeros of two linearly independent solutions of the second order equation separate each other.